Exploring the Opportunities and Challenges of the Creative Industry Post-Election: Development of the Ledre Bojonegoro Specialty Food Economic Sector - Putri, Putri Dharma Yanti; Rifa’i, Moch. Nur Aziz; Yanti, Putri Dharma (Prosiding Seminar Nasional Ilmu Manajemen, Ekonomi, Keuangan dan Bisnis, 2024)
The aim of this research is to explore the opportunities and challenges of the creative industry after the election, with a focus on the development of the Ledre specialty food economic sector in Bojonegoro. Using a qualitative approach, the author conducted in-depth interviews with business actors. We also conducted field observations and secondary data analysis. The research results show that the Ledre industry has great potential to be developed into a regional superior product, but still faces challenges related to marketing, product innovation and community empowerment. The implication is that the creative industry of typical Ledre food will not see any changes or new innovations. So government support, stakeholder collaboration, and increasing the capacity of business actors are needed to take advantage of post-election opportunities and encourage creative economic growth in Bojonegoro.